2020
DOI: 10.3390/ani10020266
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Camellia oleifera Cake Polysaccharides on Growth Performance, Carcass Traits, Meat Quality, Blood Profile, and Caecum Microorganisms in Yellow Broilers

Abstract: Simple Summary: Plant originated polysaccharides used as feed additives have gradually become popular for the health and nutrition of broilers. In the present study, polysaccharides from Camellia oleifera cake (CCP) were added to the daily diet of yellow broilers. Our results indicated that the immunity of the broilers was boosted due to the increasing weight or index of gizzard, spleen, and the thymus. CCP treatment improved the juiciness and changed the meat color of broilers by increasing the cooking loss a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 48 publications
2
17
0
Order By: Relevance
“…In previous studies, it has been demonstrated that polysaccharides had the potential to enhance the growth performance of broilers (17,18) (Figure 1). It was reported that higher-dose polysaccharides supplemented in diets were beneficial to promote growth performance, while the effects of lower-dose polysaccharides were of no significance (19). Wu (17) suggested that a diet supplemented with 500, 1,000, and 2,000 mg/kg of Astragalus membranaceus polysaccharide (APS) effectively enhanced the body weight gain of broilers after a 6-week feeding trial.…”
Section: Performance Productivitymentioning
confidence: 99%
See 3 more Smart Citations
“…In previous studies, it has been demonstrated that polysaccharides had the potential to enhance the growth performance of broilers (17,18) (Figure 1). It was reported that higher-dose polysaccharides supplemented in diets were beneficial to promote growth performance, while the effects of lower-dose polysaccharides were of no significance (19). Wu (17) suggested that a diet supplemented with 500, 1,000, and 2,000 mg/kg of Astragalus membranaceus polysaccharide (APS) effectively enhanced the body weight gain of broilers after a 6-week feeding trial.…”
Section: Performance Productivitymentioning
confidence: 99%
“…Enteromorpha polysaccharide administration increased the relative weight of the bursa of Fabricius in broilers (34) and improved the morphology of the bursa of Fabricius, including infiltration of inflammatory cells, destruction of the cell structure, and cell necrosis (35). It has been demonstrated that Camellia oleifera cake polysaccharides increased the weight or index of the spleen and thymus of broilers (19). Polysaccharides were also benefited to improve the T-lymphocyte percentage and enhance the development of immune organs, evidenced by the increased lymph follicle area in the bursa of Fabricius and white pulp area expansion, which suggested that polysaccharide treatment elicited lymphocyte formation in the bursa of Fabricius (36).…”
Section: Immnune Organ and Serum Immunoglobulinmentioning
confidence: 99%
See 2 more Smart Citations
“…D-gal has been broadly used to replicate the animal aging model. In the present study, D-gal-induced aging model in mice was built in accordance with the protocols reported in the existing investigation (Wang, Zhang, et al, 2020;Wang, Huo, et al, 2020) COCP-H group. Except that the mice in NC group were administered normal saline, mice in other groups were intraperitoneally injected with D-gal (500 mg/kg•bw) once a day for 6 weeks.…”
Section: Animal Experiments Designmentioning
confidence: 99%